Dimensi Financial Stress :: Food dan Bevarage yang Terdaftar di Bursa Efek Indonesia - Kesy Derseng Paulang (Insan Cita Bongaya Research Journal, 2024)
This study aims to examine the effect of good corporate governance on financial stress. The research was conducted on manufacturing companies in the food & beverage sector listed on the Indonesia Stock Exchange in 2020-2022. The number of samples is 31 companies and financial report data is observed for 3 years, so that the number of data observed is 93 financial statements. Data analysis uses regression analysis techniques. The results of the study show that good corporate governance has no effect on financial stress.